2015
DOI: 10.3233/jnd-150097
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Communication between Muscle Stem Cells and their Environment with Aging

Abstract: Aging is associated with both muscle weakness and a loss of muscle mass, contributing towards overall frailty in the elderly. Aging skeletal muscle is also characterised by a decreasing efficiency in repair and regeneration, together with a decline in the number of adult stem cells. Commensurate with this are general changes in whole body endocrine signalling, in local muscle secretory environment, as well as in intrinsic properties of the stem cells themselves. The present review discusses the various mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 139 publications
0
15
0
Order By: Relevance
“…3). We have found data about altered genomic instability [130], telomere attrition [89, 131], epigenetic alterations [132], loss of proteostasis and deregulated nutrients [88], mitochondrial dysfunction [133, 134], cellular senescence and stem cell exhaustion [85] and altered cell communication [135]. Along this line, different studies using heterochronic parabiosis experiments elegantly demonstrated that environmental factors influence stem cell functions [136]; exposure of stem cells to systemic factors from young mice increased their proliferative capacity.…”
Section: Resultsmentioning
confidence: 99%
“…3). We have found data about altered genomic instability [130], telomere attrition [89, 131], epigenetic alterations [132], loss of proteostasis and deregulated nutrients [88], mitochondrial dysfunction [133, 134], cellular senescence and stem cell exhaustion [85] and altered cell communication [135]. Along this line, different studies using heterochronic parabiosis experiments elegantly demonstrated that environmental factors influence stem cell functions [136]; exposure of stem cells to systemic factors from young mice increased their proliferative capacity.…”
Section: Resultsmentioning
confidence: 99%
“…Cells with highest expression of NUMB , an antagonist of NOTCH signaling, go back in quiescence for later self-renewal ( 206 ). Daughter cells in which p38α/β MAPK is asymmetrically activated by a so-called PAR complex, undergo commitment to myogenic differentiation ( 207 ), expand in number and form binuclear myotubes or fuse to existing fibers ( 168 , 199 , 203 , 208 ).…”
Section: How Healthy and Dm Muscles Are Built And Maintainedmentioning
confidence: 99%
“…During normal healthy life, this whole cascade of steps for the regulation of muscle differentiation and maintenance is orchestrated by a multitude of circulating hormones, such as IGFs, FGFs, TGFs, testosterone, thyroid hormones, cytokines, and exosome-secreted signals, which are secreted locally and appear in the muscle stem cell niches. Whether and how hormonal signaling controls viability, performance and half-life of multinucleated myofibers—i.e., the bulk of muscle mass in a healthy individual—is still poorly understood, as attention of study thus far has been mainly directed toward MuSCs ( 208 ).…”
Section: How Healthy and Dm Muscles Are Built And Maintainedmentioning
confidence: 99%
“…ageing) and pathological contexts (e.g. neuromuscular disorders, cachexia associated with cancer, etc) [44][45][46][47]. It may also provide new insights regarding the pathological mechanisms underlying such conditions and may help in the identification of novel biomarkers and novel therapeutic targets for diseases.…”
Section: Resultsmentioning
confidence: 99%